2012
DOI: 10.1007/s11999-012-2439-8
|View full text |Cite
|
Sign up to set email alerts
|

L5 Pedicle Length Is Increased in Subjects With Spondylolysis: An Anatomic Study of 1072 Cadavers

Abstract: Background In spondylolisthesis, it is believed that as L5 slips on S1, the pedicle may become elongated in response to the instability in an attempt to bridge the defect. Whether patients with spondylolysis, which is largely developmental, also develop elongation of the pedicles is unknown. Questions/purposes The purpose of this study is to evaluate and quantify the increase in L5 pedicle length in subjects with spondylolysis as compared with normal healthy subjects. Methods Nine hundred fifty-two human cadav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…The results of the present study add to the limited available data on the morphology of the L5 pedicle in subjects with spondylolytic spondylolisthesis 5,6 . Anatomic pedicle changes in spondylolytic spondylolisthesis may reflect remodeling, greater changes being associated with a greater degree of slip.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The results of the present study add to the limited available data on the morphology of the L5 pedicle in subjects with spondylolytic spondylolisthesis 5,6 . Anatomic pedicle changes in spondylolytic spondylolisthesis may reflect remodeling, greater changes being associated with a greater degree of slip.…”
Section: Discussionsupporting
confidence: 58%
“…In an anatomic study of 1072 cadavers, the L 5 pedicle length in 120 specimens with spondylolysis was compared with that of 952 controls without spondylolysis. It was found that the average pedicle length was greater in subjects with spondylolysis, and that elongation occurred after 40 years of age. However, this study was limited to cadavers, and the results and observations may not be directly applicable to living humans.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…30 This finding is consistent with the previous study where a total of 509 fetal specimens were examined and displayed neither isthmic crack nor separate neural arch. 15,[47][48][49][50] One good example is a study where the transverse interfacet distance was measured among 39 patients with spondylolysis and compared to 42 adults without spondylolysis. A, Representative calcein double labeling images of isthmus in the junctional region (boxed area) between the ventral and dorsal part of the vertebra.…”
Section: Discussionmentioning
confidence: 99%